2005
DOI: 10.1055/s-2005-864094
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Sugiol, A Diterpene Isolated fromCalocedrus formosanaBark

Abstract: Sugiol is a diterpene which was isolated and purified from alcohol extracts of the bark of Calocedrus formosana Florin (Cupressaceae). Although sugiol has low inhibitory activity against the DPPH radical, it could effectively reduce intracellular reactive oxygen species (ROS) production in lipopolysaccharide (LPS)-stimulated macrophages. The present study investigated the potential anti-inflammatory activity of sugiol, and the relationship between signal transduction and inflammatory cytokines in vitro. A dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…88 Sugiol (44), a diterpene from Calocedrus formosana bark was reported to inhibit ROS, pro-IL-1b, IL-1b, and TNF-a production and suppressed the activation of MAPKs, including extracellular signalregulated kinase (ERK), JNK, and p38 in stimulated J774A.1 murine macrophages. 89 Triptolide (45) and tripdiolide (46), diterpene epoxides isolated from Tripterigium wilfordii, down-regulated the COX-2, iNOS, and IL-1b gene expression in LPS-stimulated macrophages. 90 Clinical studies have been performed on the extract of T. wilfordii and substantial work has been reported on triptolide and celastrol (47) (Fig.…”
Section: Terpenoidsmentioning
confidence: 99%
“…88 Sugiol (44), a diterpene from Calocedrus formosana bark was reported to inhibit ROS, pro-IL-1b, IL-1b, and TNF-a production and suppressed the activation of MAPKs, including extracellular signalregulated kinase (ERK), JNK, and p38 in stimulated J774A.1 murine macrophages. 89 Triptolide (45) and tripdiolide (46), diterpene epoxides isolated from Tripterigium wilfordii, down-regulated the COX-2, iNOS, and IL-1b gene expression in LPS-stimulated macrophages. 90 Clinical studies have been performed on the extract of T. wilfordii and substantial work has been reported on triptolide and celastrol (47) (Fig.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Most known naturally occurring abietane-type diterpenes have been extracted and identified from species like C. japonica, Taiwania cryptomerioides, Thuja standishii, Juniperus formosana, Cephalotaxus harringtonia, and Vitex rotundifolia [16], [17]. In conclusion, we identified 7 diterpenes from the conifer C. japonica with anti-androgenic effects on PCa 22Rv1-derived 103E cells.…”
mentioning
confidence: 92%
“…Despite the high resemblance in chemical conformations of these diterpenes, their dramatic differ- ences in AR inhibition may provide a structure-activity relationship (SAR) for future studies. Compounds 3 and 4 have frequently been reported to have antimicrobial, antiproliferative and cytotoxicity activities [17], [18], [19]. However, compound 2 has only been reported to have antimicrobial activity, and compound 7 has no known biological effects [19].…”
mentioning
confidence: 99%
“…Our previous study reported that sugiol exhibits very weak antitumor activity against SW620 (colon), MDA-MB-231 (breast) and NCI-H23 (lung) cells [23]. Many studies investigated the biological activities of sugiol, including its modest anti-tumor [24], anti-inflammatory [25], antimicrobial [26] and aldose reductase inhibitory activities [27], its specific mechanism of action is not known.…”
Section: Introductionmentioning
confidence: 99%